THE INFLUENCE OF LEADERSHIP, COMPENSATION, AND SANCTIONS ON THE WORK DISCIPLINE OF CIVIL SERVANTS AT THE SECRETARIAT OF THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) BARRU REGENCY - Sukmiah; Muliati (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal